Participatory appraisal of grazing resources and socio-economic profile of livestock keepers of Himachal Pradesh - Dev, Inder; Radotra, Sudesh; Misri, Bimal; Sareen, Sindhu; Pathania, M.S.; Singh, J.P. (Indian Journal of Agroforestry, 2020)
A study was undertaken to understand the socio-economic status of the livestock keepers and availability of grazing resources in different agro-climatic zones of Himachal Pradesh. The findings revealed that farmers in hilly region rear sheep, goats, cattle etc. under sedentary, semi-migratory and migratory systems to supplement family income. Average land holdings of livestock keeper was 0.63 (marginal), 1.35 (small) and 2.42 ha (large) in Himachal Pradesh. In spite of having heavy pressure on grasslands and other grazing resources, fodder cultivation is given last priority by the farmers. Area under fodder cultivation varies from 0.6 to 2.7% in kharif season and from 0.6 to 3.1% in rabi season. Some of the most important grasses prevalent in the state include Andropogon pulmis, Chrysopogon gryllus, Chrysopogon montanus, Cymbopogon martini, Dichanthium sp., Eragrostis sp. Fescue grass, Heteropogon contortus, Imperata cylindrica, Paspalum notatum, Pennisetum clandestinum, Saccharum spontaneum and Sorghum halepense. Lotus corniculatus and Trifolium sp. were observed as the dominant legume species. Chrysopogon in zone-I and II, and Festuca in zone-III were observed to be most preferred grass species. Acacia catechu, Albizia lebbeck, Albizia stipulata, Artocarpus chaplasha, Bauhinia variegata, Bombax ceiba, Cedrella toona, Celtis australis, Dalbergia sisso, Dendrocalamus hamiltonii, Ficus sp., Grewia optiva, Morus alba, Quercus sp., Robinia pseudoacacia and Terminalia alata were found most common fodder trees. In terms of palatability and increase in milk yield of animals, Grewia optiva (zone-I and II) and Morus (zone-III)Â Â  were rated as the most preferred fodder trees. Fodder trees and grazing are the two most important components of feeding in Zone-I, II and III. Grazing was the most important component of feeding animals in Zone-IV.